Archebittacus exilis Riek—the oldest hangingfly (Insecta: Mecoptera: Bittacidae) - Lambkin, Kevin J. (Zootaxa, 2017)
The Bittacidae has a rich fossil history, especially in the Jurassic. The only pre-Jurassic species ascribed to the family has been Archebittacus exilis Riek, 1955, known from several forewing and hindwing fragments from the Late Triassic (Norian) Mount Crosby Formation of Queensland. A re-examination of Riek’s type series as well as an additional hindwing specimen has found that although A. exilis has a predominance of plesiomorphies, it exhibits the following apomorphies sufficient to justify its inclusion in the Bittacidae, albeit as one of its most plesiomorphic members: wing bases narrowed (but less so than in nearly all other bittacids); R4+5→R4 at least slightly arched in forewing, but with arching more pronounced in hindwing; R5 convex; the stem of CuA in the forewing fused with M for at least a short distance; forewing costal margin straight and costal space very narrow; 2A short and simple.